Fibroblast growth factor-23 is an independent predictor of hospitalization for heart failure and major cardiovascular adverse events in patients undergoing cardiac surgery. (3rd October 2022) - Hofer, F; Hammer, A; Kazem, N; Koller, L; Steinacher, E; Steinlechner, B; Laufer, G; Niessner, A; Sulzgruber, P
Abstract: Background: Fibroblast growth factor 23 (FGF-23) plays a crucial role in regulating phosphate and vitamin D metabolism and was proved to be associated with an increased risk for fatal events in individuals suffering from cardiovascular diseases. Since data on the prognostic potential of FGF-23 in individuals undergoing cardiac valve and/or coronary artery bypass graft (CABG) surgery are scarce, the specific objective of this study was to investigate the impact of FGF-23 on postoperative complications, particularly postoperative atrial fibrillation (POAF), hospitalization for heart failure (HHF) and cardiovascular (CV) death in an unselected patient population after cardiac surgery. Methods: Within the present investigation, patients undergoing elective cardiac valve and/or CABG surgery were prospectively enrolled at the Department of Cardiac Surgery of a medical university. Blood samples were taken prior to surgery and FGF-23 concentrations were subsequently assessed. Patients were followed prospectively until the primary study endpoint (CV death) was reached. Results: In total, 462 patients were included in the present analysis and followed over a median of 3.9 years. During follow-up 67 (14.5%) patients died. The patients' median age was 70 years (interquartile range [IQR] 60 to 75) and 133 (28.8%) were female. The median FGF-23 level in the entire study population was 1.9 pmol/L (IQR 1.2 to 3.5). Notably, individuals with POAF showed significantly higher FGF-23 levels than patients without (p<0.001). After stratification into tertiles (T) of FGF-23 patients in the highest FGF-23 tertile showed greater rates of HHF, all-cause and CV death. Furthermore, FGF-23 was consistently associated with POAF development showing an adjusted OR for a 1-unit increase in standardized log-transformed biomarker of 1.28 (95% CI: 1.01 to 1.63), along with an adjusted OR of 2.04 (95% CI 1.33 to 3.13, p=0.001) for the pre-defined high risk cut-off value. A steady risk increase for HHF and CV death among ascending FGF-23 tertiles has been noted. Moreover FGF-23 showed strong discriminatory performance (area under the curve [AUC] 0.69, 95% CI 0.61–0.77). Reclassification analysis indicated that the addition of FGF-23 to NT-proBNP provides a significant improvement in risk discrimination (NRI at the event rate: 0.58, 95% CI 0.34–0.81, p-value <0.001; IDI: 0.03, 95% CI 0.01–0.05, p-value= 0.001). Conclusion: FGF-23 proved to be a strong and independent predictor for POAF, HHF and CV death in individuals undergoing cardiac surgery. Considering an individualized risk assessment, routine preoperative FGF-23 evaluation may improve detection of patients at risk, who require in-depth clinical attention throughout the peri- and postoperative phase after cardiac surgery. Funding Acknowledgement: Type of funding sources: None.